2013
DOI: 10.1371/journal.pone.0071386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Rickettsia typhi in Cats and Fleas

Abstract: Background Rickettsia typhi is the etiological agent of murine typhus (MT), a disease transmitted by two cycles: rat-flea-rat, and peridomestic cycle. Murine typhus is often misdiagnosed and underreported. A correct diagnosis is important because MT can cause severe illness and death. Our previous seroprevalence results pointed to presence of human R . typhi infection in our region; however, no clinical case has been reported. Although cats have been related to MT, no naturally infected cat has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 27 publications
0
34
1
Order By: Relevance
“…Based on the results of the study described herein, it appears unlikely that domestic cats are an effective reservoir host for R. typhi and it is possible that other animals work as reservoir hosts for R. typhi (Eisen and Gage ). However, 15.8% prevalence in naturally infected cats was found in a recent study carried out in northeast Spain (Nogueras et al This discrepancy between the two studies might be due to the different origin of the cats involved (veterinary clinics vs veterinary clinics, shelters, and the street) or the sample area. A high variability in prevalence (none vs 62.9%) was observed according to the area sampled (Nogueras et al It is important to maintain a high level of surveillance for this infectious disease.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Based on the results of the study described herein, it appears unlikely that domestic cats are an effective reservoir host for R. typhi and it is possible that other animals work as reservoir hosts for R. typhi (Eisen and Gage ). However, 15.8% prevalence in naturally infected cats was found in a recent study carried out in northeast Spain (Nogueras et al This discrepancy between the two studies might be due to the different origin of the cats involved (veterinary clinics vs veterinary clinics, shelters, and the street) or the sample area. A high variability in prevalence (none vs 62.9%) was observed according to the area sampled (Nogueras et al It is important to maintain a high level of surveillance for this infectious disease.…”
Section: Discussionmentioning
confidence: 86%
“…Two cycles are involved in R. typhi transmission: a classical cycle that involves rats as a reservoir and Xenopsylla cheopis as a vector, and a peridomestic cycle, involving cats, dogs, peridomestic rodents, and their fleas, Ctenocephalides felis ) (Gillespie et al In Spain, some epidemiological studies have shown a seroprevalence of R. typhi of up to 18% in human populations (Santibáñez et al Although the maintenance of R. typhi in the peridomestic cycle is of potential public health importance and a major health risk, the extent of exposure to this pathogen remains incompletely described in cats and their fleas. In Spain, only one study conducted in northeast Spain provides information related to R. typhi infection in cats and their fleas (Nogueras et al …”
Section: Introductionmentioning
confidence: 99%
“…were found in IDUs from Harlem . In our region, a cycle involving pets has been described . Thus, it may be incorrect to postulate a higher risk among people with poor living conditions than among people living in homes.…”
Section: Clinical Data Of Hiv‐infected Subjects Tested For R Typhi Amentioning
confidence: 67%
“…Presence of DNA of either R. typhi or R. felis had been analyzed previously in Ctenocephalides felis collected from cats and dogs that had been attended at a veterinary clinic (Nogueras et al 2011(Nogueras et al , 2013a. Fleas had been individually triturated in 100 lL of brain-heart infusion (BHI).…”
Section: Evaluation Of Antibioticsmentioning
confidence: 99%
“…MT is one of the most prevalent Rickettsioses worldwide distributed (CDC 2009;Dzul-Rosado et al 2013;Gillespie et al 2009;Nogueras et al 2013a;Phongmany et al 2006;Znazen et al 2013); however, its real prevalence is unknown in many countries. MT is usually a mild and acute disease, whose main clinical signs are fever and rash.…”
Section: Introductionmentioning
confidence: 99%